Practical tuberculosis teaching in nursing schools, Brazil – 2004 - Villa, Tereza CS; Firmino, Danuza R; Andrade, Rubia LP; Brunello, Maria EF; Oliveira, Mayra F; Ruffino-Netto, Antônio (Online Brazilian Journal of Nursing, 2006)
Objective: To analyze practical tuberculosis (TB) teaching in Nursing Schools (NS) in Brazil in 2004. Methodology: We surveyed all NS in Brazil in 2004, and sent questionnaires by mail to faculty TB teaching. Data were compiled in a database with a view to descriptive analysis. In a universe of 347 NS, 111 answered the questionnaire, which constituted the study population. Results: 75,2% of the NS are concentrated in the Southeast and South. The hour load (HL) for practical TB teaching ranges between 10 and 20 hours (42,2%). Teaching is mainly provided (89,1%) at primary care level. Practical activities focus on nursing appointments and home visits. Faculty members obtain updated knowledge on the subject through scientific events and Internet. Conclusion: The student training in TB care isn’t enough to discuss aspects of treatment, epidemiological surveillance and management.